2019
DOI: 10.14710/nmjn.v9i1.22822
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Factors of Interpersonal and Situational Influences for Performing Stretching Exercises Based on Pender’s Model

Abstract: Background: Physical activity affects office employees in achieving a healthy lifestyle and preventing diseases such as Musculoskeletal Diseases (MSDS). Combining sports such as stretching exercises in healthy lifestyle programs is one of the most important decisions to prevent such disease.Purpose: This study aimed to predict factors of interpersonal and situational influences for stretching exercise (SE) among office employees at Shahid Beheshti University of Medical Sciences.Methods: A cross-sectional study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…referring to the extraction factor 4 and 6 as interpersonal influences 1 and 2, which could make up a total of 8·64 % of the total variance of the model, can indicate the predictive power of this construct in the present study in understanding consumer behaviour. F&V were in line with the results of a study by Delshad et al In Tehran, Iran, which showed that government employees who had more interpersonal influence were more likely to engage in the health behaviour studied (stretching exercise) ( 61 ) . Accordingly, the results of Guadagnin et al can be mentioned in relation to the importance of the construct validation for development of an accurate instrument.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…referring to the extraction factor 4 and 6 as interpersonal influences 1 and 2, which could make up a total of 8·64 % of the total variance of the model, can indicate the predictive power of this construct in the present study in understanding consumer behaviour. F&V were in line with the results of a study by Delshad et al In Tehran, Iran, which showed that government employees who had more interpersonal influence were more likely to engage in the health behaviour studied (stretching exercise) ( 61 ) . Accordingly, the results of Guadagnin et al can be mentioned in relation to the importance of the construct validation for development of an accurate instrument.…”
Section: Discussionsupporting
confidence: 89%
“…In order to achieve better results in the present study, a cut-off point of 0•40 was used as a criterion for high correlation between items. The results demonstrated that the majority of items (88•13) had a high correlation and hence remained in the study, while (61) . Accordingly, the results of Guadagnin et al can be mentioned in relation to the importance of the construct validation for development of an accurate instrument.…”
Section: Discussionmentioning
confidence: 90%
“…Interpersonal in uences are de ned as cognitions concerning the behaviors, beliefs, or attitudes that decide individuals' predisposition to involve in healthy behaviors (47). The social support was considered as a measure of interpersonal in uences.…”
Section: Discussionmentioning
confidence: 99%
“…Interpersonal in uences are de ned as cognitions concerning the behaviors, beliefs, or attitudes that decide individuals' predisposition to involve in healthy behaviors (47). The social support was considered as a measure of interpersonal in uences.…”
Section: Discussionmentioning
confidence: 99%